ChemInform Abstract: Formal C—H Amination of Cyclopropenes. Issue 10 (7th March 2013) - Sun, Chunrui; Li, Jingwei; Lee, Daesung; Huang, Genping; Xia, Yuanzhi
Abstract Tms‐Substituted cyclopropene derivatives are treated with azo ester (II) to afford ring‐aminated derivatives.